2023
DOI: 10.1108/jfra-10-2022-0383
|View full text |Cite
|
Sign up to set email alerts
|

CEO masculine behavior and earnings management: does ethnicity matter?

Abstract: Purpose This study aims to investigate the relationship between the Chief Executive Officers (CEOs’) masculinity, CEO characteristics (accounting background, turnover and ethnicity/race) and earnings management (EM) in Malaysia. It also examined the moderating effect of the CEOs’ ethnicity/race (Bumiputera and non-Bumiputera) on the relationship between CEO masculinity and EM. Design/methodology/approach The analyses were based on a panel data set of 260 corporates listed on the Bursa Malaysia from 2009 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Several studies also affirm that firms' ED and ESGR is a response to the expectations of various stakeholders based on the legitimacy theory [ 14 , 39 , 40 ]. Some other studies suggest that the purpose of high-quality disclosure is based on voluntary disclosure theory [ 2 , 10 , 13 , 27 , 30 , 32 ] where companies demonstrate their performance [ 9 , 10 , 15 , 19 , 32 , 41 ]. Zeng et al [ 42 ] suggested that businesses that are environmentally conscious and have a strong reputation are more likely to provide more ED.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies also affirm that firms' ED and ESGR is a response to the expectations of various stakeholders based on the legitimacy theory [ 14 , 39 , 40 ]. Some other studies suggest that the purpose of high-quality disclosure is based on voluntary disclosure theory [ 2 , 10 , 13 , 27 , 30 , 32 ] where companies demonstrate their performance [ 9 , 10 , 15 , 19 , 32 , 41 ]. Zeng et al [ 42 ] suggested that businesses that are environmentally conscious and have a strong reputation are more likely to provide more ED.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the profound and long-term global impact of sustainability issues and the SDGs, it emphasizes the need for knowledge that benefits not only corporations in understanding the potential influence of ESG disclosure but also supports national and international efforts to create a more desirable social environment and address climate change. Finally, continuous engagement with relevant stakeholders is identified as essential for fostering a positive environment that drives ongoing improvements in ESG disclosures (Adams et al , 2014; Bose et al , 2022; Ellili, 2022; Elsheikh et al , 2023).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Although, previous literature provides evidence of how board characteristics influence EM practices in large enterprises (Abdou et al , 2021; Alves, 2023; Chatterjee and Rakshit, 2023; Chee and Tham, 2021; Cho and Chung, 2022; Cornett et al , 2009; Elsheikh et al , 2023; Goel and Kapoor, 2022; Liu and Lu, 2007; Mensah and Boachie, 2023; Mensah and Onumah, 2023; Musa et al , 2023; Prencipe and Bar-Yosef, 2011; Widagdo et al , 2022; Roy and Alfan, 2022; Sáenz González and García-Meca, 2014; Sehrawat et al , 2019; Sultana et al , 2017) and EM practices in small- and medium-sized enterprises (SMEs) (Balachandran et al , 2021; Chansarn and Chansarn, 2016; Chiu and Wei-Hua, 2020; Duarte, 2022; Gajdosikova et al , 2022; Gandía and Huguet, 2021; Höglund and Sundvik, 2016; Huang et al , 2022; Maglio et al , 2020; Martinez-Martinez et al , 2021; Park et al , 2021; Séverin and Veganzones, 2021). However, there is little research examining the link between the roles of BOD and earning management practices among SMEs (Chiu and Wei-Hua, 2020 and Maglio et al , 2020) and none specifically examines such relation among SMEs operating in the UK context.…”
Section: Introductionmentioning
confidence: 99%